A new and sensitive co-operational polymerase chain reaction for rapid detection of Ralstonia solanacearum in water - Caruso, Paola; Bertolini, Edson; Cambra, Mariano; López, María M. (2017)
Three primers from 16S rRNA were successfully assayed simultaneously in one reaction for sensitive detection of Ralstonia solanacearum in watercourses. The protocol is a modification of the Co-operational polymerase chain reaction (Co-PCR), which allows the simultaneous and co-operational action of the primers. It specifically amplified R. solanacearum strains belonging to biovars 1, 2 and 4. No products were obtained from any of the 162 unidentified isolates from river water. The sensitivity of the assay was <1 cfu/ml as determined by analysis of heat-treated water samples spiked with R. solanacearum, also containing indigenous microbiota up to 105 cfu/ml. The developed Co-PCR assay was more sensitive than other standard PCR assays in the analysis of 51 Spanish environmental water samples. Namely 31.3% of the samples were positive using the newly developed assay, whereas 13.7% or less positive samples were found with the other protocols. The Co-PCR improves the detection sensitivity of R. solanacearum and provides an important tool for its routine detection from environmental water samples and for epidemiological studies.